A Web-based collaborative design modeling environment - Pahng, GDF; Bae, SH; Wallace, D (SEVENTH IEEE INTERNATIONAL WORKSHOPS ON ENABLING TECHNOLOGIES: INFRASTRUCTURE FOR COLLABORATIVE ENTERPRISES (WET ICE '98), 1998)
This paper presents an open product development environment for distributed, collaborative, and integrated design. The web-based framework, called DOME, allows designers to build integrated models using both local and distributed resources, and to collaborate by exchanging services in a network-centric environment. An integrated model can be created while each participant focuses on their own area of expertise. A design problem model is created by connecting modules, each of which can represent specific components, analysis capabilities/softwave, disciplines, or organizations relevant to the problem. The resulting module network forms a concurrent model in which changes propagate through service exchanges. A Java applet-based user interface provides cross-platform and distributed user access to DOME module servers throughout the network.